Optimizing e-modules in Early Childhood Motoric Courses in the PG PAUD Study Program, Universitas Negeri Medan - Rizki Ramadhani; Kamtini Kamtini; Gita Noveri Eza; Damaiwaty Ray; Nasriah Nasriah (Budapest International Research and Critics University, 2022)
This study aims to analyze online learning in early childhood motoric development methodology courses using e-modules of practical materials in the PG PAUD FIP UNIMED study program. This study uses qualitative descriptive with qualitative analysis in a research activity with research subjects PG PAUD semester V 2019. Data collection techniques are carried out by observation, documentation and interviews. The results showed that, through observations distributed through questionnaires, interviews were conducted through online learning through the use of e-modules in the early childhood motor development methodology course. can be a good alternative in online learning during a pandemic and can improve students' abilities in aud music practice courses as well as from documentation through videos that students are able to follow and use e-modules. From the results of field practice analysis conducted virtually, it shows that online learning through zoom and the use of this e-module application can improve the ability of students both individually and in groups in learning motoric methodologies for early childhood.